Mineral fertilization and Mononychellus tanajoa population in cassava - Farias, Alba Rejane Nunes; Zem, Antonio Carlos; Gomes, Jayme de Cerqueira; Macedo, Manuel Claudio Motta; Flechtmann, Carlos H.W. (Pesquisa Agropecuaria Brasileira, 2014)
The mite Mononychellus tanajoa is a serious problem for the cassava crop in tropical regions, causing defoliation and death of the terminal bud of the plant. One of the factors involved with this mite population is the nutritional status of plants. A trial involving NPK fertilization was carried out in greenhouse, with the plants being watered regularly, and the results showed a negative relationship between N + P and N + P+ K applied to soil, and the occurrence of the green mite. An opposite trend was observed in relation to fertilization and dry matter production (aerial pan).